Effect of nursery intrasurgical intervention in postquirurgic pain level - Pilar Ureña Ceruelo; María Teresa Urdiales Gutiérrez; África Negueruela Ordoqui; Margaret Pompeya González Alonso; María Rocío López Sanz; Trinidad Fernández Sánchez (Fundación para el Desarrollo de la Enfermería, 2009)
A patient who is admitted or is going to be operated, feels himself in a reality that might be perceived as a threat, and therefore, might cause an anxiety feeling. The anxiety level influences the perception of the pain the post-surgery period.There are several interventions to decrease the anxiety level, but they are not set on the same scientific evidence level.The aim of this study is to know if some specific interventions carried out by nurses during surgery reduce the patient's pain during the post-surgery period.So, a randomised controlled trial has been designed, composed by two groups of patients who are will undergo a surgery with epidural anaesthesia. Pain intensity will be assessed during the first 48 hours after surgery, as well as the painkiller consumption and we will compare obtained data between the group who had received the nursery intervention and the control group.